Treating Alpelisib-Induced Hyperglycemia with Very Low Carbohydrate Diets and Sodium-Glucose Co-Transporter 2 Inhibitors: A Case Series. (July 2021) - Blow, Tahj; Hyde, Parker N.; Falcone, John N.; Neinstein, Aaron; Vasan, Neil; Chitkara, Ritika; Hurd, Maurice A.; Sardesai, Sagar; Lustberg, Maryam B.; Flory, James H.; Volek, Jeff S.; Goncalves, Marcus D.
Alpelisib is a α-selective phosphatidylinositol 3-kinase (PI3K) inhibitor approved for treatment of postmenopausal women, and men, with hormone receptor positive (HR+), human epidermal growth factor receptor 2 negative (HER2–), PIK3CA-mutated, advanced breast cancer (ABC). Hyperglycemia is a common, on-target adverse effect that impairs treatment efficacy and increases the rate of treatment delays, dose reductions, and discontinuation. Currently, there are no clear guidelines on how to manage hyperglycemia due to alpelisib when metformin is not effective. In this case series, we review 3 subjects with ABC that developed hyperglycemia during alpelisib-fulvestrant therapy and were successfully managed with dietary and pharmacologic interventions. These cases provide anecdotal evidence to support the use of sodium-glucose co-transporter-2 inhibitors (SGLT2i) and very low carbohydrate diets to minimize hyperglycemia during alpelisib therapy.